On-demand orbital maneuver of multiple soft robots via hierarchical magnetomotility - Sukyoung Won (Nature Portfolio, 2019)
Magnetic soft robots show advantages in wireless actuation, but normally demand complicated device preparations and three-dimensional magnetic manipulation. Won et al. show helical soft robots responsive to a magnetic field rotating along a single axis, whose velocity and orbits can be controlled independently.